Daily consumption of a dark-roast coffee for eight weeks improved plasma oxidized LDL and alpha-tocopherol status: A randomized, controlled human intervention study. (May 2019) - Hochkogler, Christina M.; Schweiger, Kerstin; Rust, Petra; Pignitter, Marc; Rathmayr, Johanna; Bayer, Sebastian; Chmelirsch, Christina; Hüller, Leonie; Marko, Doris; Lang, Roman; Hofmann, Thomas; Kurz, Andrea Christina; et al.
Graphical abstract: Highlights: Consumption of dark-roast coffee improves the intake of antioxidants. Dark roast coffee constituents other than antioxidants may improve plasma antioxidant status. Drinking dark-roast coffee improved plasma oxLDL and α-tocopherol likely through lipolysis. Abstract: Scope: Coffee consumption is widely recognized to improve the antioxidant status. We hypothesized a dark-roast coffee to reduce plasma oxidized LDL (oxLDL) and to improve alpha-tocopherol concentrations. Methods and results: After a 4 week, coffee-free run-in period, 86 healthy, randomized volunteers completed either a control (CTRL) or coffee (COFF) intervention in which either 750 mL water (CTRL) or coffee (COFF) were consumed daily for 8 weeks. Blood samples were taken at the begin and after the intervention. Mean changes in oxidized LDL concentrations after coffee consumption (−0.47 ± 15.4 U/L) differed from those of the CTRL-G (5.69 ± 18.8 U/L, p < 0.05). Levels of alpha-tocopherol (+3.46 ± 16.48%, p < 0.05) as well as non-esterified fatty acids increased in the COFF-G. Conclusion: Improved plasma alpha-tocopherol levels and reduced levels of plasma oxLDL after 8 week consumption of a dark-roast coffee rich in N-methylpyridinium are hypothesized to be caused by coffee-induced lipolysis, resulting in increased alpha-tocopherol mobilisation.